Pharmacogenetics research on chemotherapy resistance in colorectal cancer over the last 20 years - Panczyk, Mariusz (Baishideng Publishing Group Inc, 2014)
During the past two decades the first sequencing of the human genome was performed showing its high degree of inter-individual differentiation, as a result of large international research projects (Human Genome Project, the 1000 Genomes Project International HapMap Project, and Programs for Genomic Applications NHLBI-PGA). This period was also a time of intensive development of molecular biology techniques and enormous knowledge growth in the biology of cancer. For clinical use in the treatment of patients with colorectal cancer (CRC), in addition to fluoropyrimidines, another two new cytostatic drugs were allowed: irinotecan and oxaliplatin. Intensive research into new treatment regimens and a new generation of drugs used in targeted therapy has also been conducted. The last 20 years was a time of numerous in vitro and in vivo studies on the molecular basis of drug resistance. One of the most important factors limiting the effectiveness of chemotherapy is the primary and secondary resistance of cancer cells. Understanding the genetic factors and mechanisms that contribute to the lack of or low sensitivity of tumour tissue to cytostatics is a key element in the currently developing trend of personalized medicine. Scientists hope to increase the percentage of positive treatment response in CRC patients due to practical applications of pharmacogenetics/pharmacogenomics. Over the past 20 years the clinical usability of different predictive markers has been tested among which only a few have been confirmed to have high application potential. This review is a synthetic presentation of drug resistance in the context of CRC patient chemotherapy. The multifactorial nature and volume of the issues involved do not allow the author to present a comprehensive study on this subject in one review.